Investigating the deployability of VoIP services over wireless interconnected micro aerial vehicles. Issue 5 (23rd April 2018) - Sanchez‐Aguero, Victor; Nogales, Borja; Valera, Francisco; Vidal, Ivan
Abstract : Emerging technological devices, such as Unmanned Aircraft Vehicles (UAV) and Single Board Computers (SBC), are being increasingly employed in recent years, thanks to the advances in electronics and the wide variety of sensors that are endowed. This paper aims at analyzing the viability of deploying multimedia services, focusing on the voice scenario, over wireless interconnected Micro Air Vehicles (MAV), also known as drones. Toward this end, we assessed the performance both of the embedded wireless cards of current drones and also SBCs, which may be carried as payload in existing UAV solutions. Driven by the results obtained in these experiments, we then deployed an operational VoIP service over a network of commercial MAVs, to perform an experimental analysis on the resource capabilities of these devices and demonstrate that this type of service can certainly be used.